Temperature Difference in Loading Area (Tarmac) during Handling of Air Freight Operations and Distance of Production Area Affects Quality of Fresh Mango Fruits (Mangifera indica L. Nam Dok Mai Si Thong) - Kraisuwit Srisawat; Panmanas Sirisomboon; Umed Kumar Pun; Warawut Krusong; Samak Rakmae; Nattawut Chaomuang; Pornkanya Mawilai; Thadchapong Pongsuttiyakorn; Chalisa Chookaew; Pimpen Pornchaloempong (My University, 2022)
Mango (Mangifera indica L.) ‘Nam Dok Mai Si Thong’ is an important cultivar for export from Thailand. Export mainly takes place via air transport, but for about 2 h at the loading area (tarmac), unit loading devices (ULDs) are exposed to ambient environmental conditions. In this research, the effects of different temperature conditions at the loading area (tarmac) and the distance of the production area from the tarmac on the quality of fresh mango fruits were studied. The treatments included three temperature conditions for 2 h (simulated handling in tarmac)—constant temperature (20 °C), non-insulated or insulated and exposed to sun—and two distances of the tarmac from the production area—short distance (i.e., transport occurring 53 h after harvest) and long distance (i.e., transport occurring 70 h after harvest). The temperature variation in the boxes exposed to the sun was greater in the non-insulated than in the insulated boxes, but this effect was more pronounced in fruit from the short-distance production area (28.1 °C insulated and 36.9 °C non-insulated) than in fruit from the long-distance production area (34.2 °C insulated and 38 °C non-insulated). Insulation and short distance increased the shelf life, decreased weight loss, delayed the decrease in average firmness and rupture force, etc. The insulation of mango fruit boxes mitigates the deleterious effect of exposure to 2 h of direct sun by reducing the increase in temperature, thus improving the shelf life and quality of mango fruit.
Keywords: Mangifera; Postharvest Quality and Shelf Life Management